2013
DOI: 10.1016/j.bbadis.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin increases glomerular filtration barrier permeability through dimerization of protein kinase G type Iα subunits

Abstract: The increase in the permeability of the glomerular barrier filtration to albumin is a well-known feature of diabetic microvasculature and a negative prognostic factor for vascular complications. However, the underlying mechanisms are incompletely understood. We demonstrated recently that superoxide anion generation increases dimerization of protein kinase G type Iα (PKGIα) subunits, leading to podocyte dysfunction. Here we investigated whether high insulin concentration is involved in PKGI-dependent hyperperme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…Recently, we showed that activation of the NOX4 subunit of NAD(P)H oxidase induced changes in MYPT1 and MLC phosphorylation by activating PKGIa [13]. When we used changes in MLC phosphorylation to indicate PKG activity, we confirmed that INS activated PKGIa.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Recently, we showed that activation of the NOX4 subunit of NAD(P)H oxidase induced changes in MYPT1 and MLC phosphorylation by activating PKGIa [13]. When we used changes in MLC phosphorylation to indicate PKG activity, we confirmed that INS activated PKGIa.…”
Section: Discussionsupporting
confidence: 75%
“…In that model, both PKGIa and NOX4 expression were elevated. Together, those studies suggested that insulin may regulate filtration-barrier permeability, and this mechanism may be dysregulated in diabetes [13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…We previously demonstrated that insulin increased the activation of PKGIα subunits, which led to podocyte dysfunction [21]. We found relationships between PKGIα activation, oxidative stress, actin reorganization, and changes in the permeability of the filtration layer to albumin [22].…”
Section: Introductionmentioning
confidence: 86%
“…Actin reorganization leads to changes in podocyte structure, and insulin receptor stimulation causes the retraction of podocyte processes [5]. Some groups have suggested that insulin plays a role in the control of podocyte contractility, which may contribute to glomerular permeability [6][7][8][9]. We recently demonstrated that insulin remodels the actin cytoskeleton and increases the albumin permeability of both isolated rat glomeruli and podocytes; we further showed that the underlying mechanism is calcium-dependent [10,11].…”
Section: Introductionmentioning
confidence: 96%